Genetic Diversity of Duabanga moluccana Blume from Two Provenances in West Nusa Tenggara Revealed by Microsatellite markers - Siti Halimah Larekeng; Yusniar Yusniar; Muh Restu; Rismawati Rismawati; Yuni Fitri Cahyaningsih; Mirza Arsiaty Arsyad; Arif Nirsatmanto (Hasanuddin University, 2020)
Duabanga moluccana Blume, locally known as Rajumas, is a tree species that suitable for building materials, pulp, and plywood. The information about genetic diversity is required for the conserving of this species. Here, we elucidated the genetic diversity of D. moluccana from two provenances in West Nusa Tenggara, Indonesia. Four microsatellite markers successfully amplified 12 randomly selected samples and produced polymorphic DNA bands. Those primers were DMAG10, DMAG09, DMACAG01 and DMTCAC11. High genetic diversity was detected in the populations with 0.54 of mean expected heterozygosity (He). The genetic variation among individuals was 100%, whereas there were no genetic variations among populations and within individuals